PENGARUH FILSAFAT HUKUM TERHADAP PERKEMBANGAN PEMBARUAN KAIDAH-KAIDAH FIQHIYAT-USHULIYYAT - Hasan, Hamsah (Al AHKAM: Jurnal Kajian Ilmu Hukum dan Syariah, 2015)
Philosophy is activity think with aim looks for to level with another about The Infinite,Religion, Philosophy and life and human death law and in the presence nature. In consequence,in terms divinity concept in Islamic Law philosophy in level meaning digging ups illat , hikmahand hush hush aught law, not something which seeing to reduce existence and islamic lawreality besides is seen will wreck believe a Moslem. By the same token, this all still in seekingframework and reality digging up effort levels with another already be believed its truth,without keaguan little bit even, one that even with full that consciousness available hikmahhikmah obtainable with fikirs energy and nalar is man and there is unreachable with nalar butwith amaliyah. Divinity philosophy in relevansinya with islamic law philosophy is one unitarythat dont most come to pieces. Because to understand islamic law that difahami shallphilosophy divinity philosophy divinity be philosophy think meanwhile law philosophy beimplementation philosophy of divinity philosophy.